Experimental Study of the Performance of Two-way RC Slabs Retrofitted with High Performance Fibre Reinforced Cement Composite (HPFRCC) prefabricated laminates - M. Mahdi Fallah Bafghi (Iranian Society of Structrual Engineering (ISSE), 2019)
Reinforced concrete structures need to be strengthened and retrofitted for various reasons, including errors during design and/or construction, and in most cases reinforcement of structural elements is much more economical than rebuilding the structure. Using HPFRCC with tensile stiffening behaviour has been developed to reinforce the concrete structures over the recent few years. In this paper, the usage possibility of HPFRCC for reinforcing two-way reinforced concrete slabs has been studied. .A total of five two-way slabs were constructed and tested to reach the rupture stage , that one of not reinforced slabs as control slab, and the rest of the slabs were reinforced in various forms. The reinforcements were carried out in two ways, once by installing veneer in the tensile area and once by installing veneer in both tensile area and compression area each time with different percentages of the fibres. The behaviour of bending and cracking, yielding and rupture of the laboratory samples were evaluated. The results revealed that the installation of pre-fabricated laminates of HPFRCC significantly improved the bending performance of reinforced slabs, so that the deformability, energy absorbance value, resistance to cracking and initial hardness of the slabs was increased and the crack width decreased. Therefore, they can be used to reinforce the weak slabs.